Oligopoly Trends in Energy Markets: Causes, Crisis of Competition, and Sectoral Development Strategies - Hajiyev, Nazim; Mansura, Manafova; Sverdlikova, Elena; Safronov, Roman; Vityutina, Tatyana (International Journal of Energy Economics and Policy, 2021)
Uncertainty in the markets associated with COVID-19 created the need for choosing the optimal model of energy markets. At the current stage of energy markets development, oligopoly tendencies tend to prevail. The article discusses the problem of choosing an effective energy market model, using the example of the electricity market. The competitive energy market of the European Union (finalized with the adoption of the Third Energy Package) was chosen as the basic model, with which the energy markets of the Russian Federation and Azerbaijan are compared. The basic indicators of the EU market were defined and compared with similar indicators for the Russian and Azerbaijani markets. The article explored the main tendencies as well as deadweight losses for Russian and Azerbaijani markets. Recommendations for improving the competitiveness of the markets are developed. The study showed that the level of market competitiveness was directly associated with the economic security of the energy market. The ways of increasing market liberalization in Russia and Azerbaijan were proposed. The proposed gradual liberalization of electricity markets involves the transition from a closed monopolistic to an open competitive electricity market, changing the institutional structure, the search for new and effective mechanisms of interaction between the buyer and seller of electricity. It also creates an opportunity to improve the quality of electricity supply, increase the investment attractiveness of the sector at large, and reduce the cost of electricity. Keywords: degree of competition; electrical power; energy markets; European Union; market model. JEL Classifications: D43, D47 DOI: https://doi.org/10.32479/ijeep.11634